Analisis Rhodamin B Dalam Lipstick Di Kecamatan Banjarmasin Utara - Hansel Hens Tangkas; Trias S. Putri; Syarifah S. Aisyah; Hairunnisa Hairunnisa; Helda Oktavia; Indah Purnamasari; Siti Salbiah; Rahmadani Rahmadani (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: Rhodamine B is a synthetic substance which is generally used as a dye in paper, textile or ink which causes respiratory irritation and when used can cause cancer and liver damage in the body. The use of Rhodamine B for a long time will cause acute danger if swallowed and cause vomiting which causes irritation of the digestive tract and causes symptoms of poisoning. The purpose of this study was to determine the presence of lipstick containing Rhodamine B. The testing method carried out used for qualitative testing is Thin Layer Chromatography (TLC) and quantitative testing using UV-VIS Spectrophotometry. The results of the lipstick sample were qualitatively proven to contain rhodamine B with a mobile phase and a stationary phase of 70% ethanol: ammonia: ethyl acetate (5:2,5:12,5) and silica gel 254 nm. With an RF value of 0.57. In quantitative testing, rhodamine B levels were found to be 2.598 mg/L. Conclusion lipsticks circulating in the East Banjarmasin sub-district are proven to contain rhodamine B.